Klang Valley - Food Fair - Sunday Star, (2008)
Universiti Putra Malaysia s Student Representatives Council is organising a food exhibition cum fair at the Food vService Complex near the Banquet Hall in its campus in Serdang, Selangor today at 8am There will also be a career talk about the food industry at 10am.